Urban Dynamics and Networking in Coastal Cities -The case of tourism - Dimitrios Economou; Maria Vrassida (European Regional Science Association (ERSA), 2005)
Traditionally coastal cities had a role as trading ports or gates of entry connecting the hinterland other parts of the world or the country, and acting as points of departure or arrival for goods and people. Trade and industry, were the spine of the economy for many years and a network was created between ports and coastal cities in order to move people (workforce), goods, and materials. Tourism is a dynamic spontaneous phenomenon, which creates opportunities for many coastal cities to participate in a different network of exchange. Tourism is considered an activity that does not create networks in the traditional sense but as mobility increases information and familiarity could pose as a new kind of connection between coastal cities. This paper aims to explore the structure and dynamics of such a network at an inter-intra regional level. The focus is on coastal cities since they are very popular tourism destinations and they account for the majority of visits in Europe. Reference will be made to the Greek middle size coastal cities since many of their traditional activities are degrading, they already attract a large number of visitors and they provide the opportunity for regeneration through tourism. The paper will be based on a questionnaire survey of visitors conducted during the summer months (June-August 2003) in Volos a middle size coastal city in Greece. The questionnaire is part of a broader survey of tourism in Volos aiming to explore tourism characteristics, flows and to evaluate the tourism product of the city. This network relationship will be examined in terms of complementary and competition and the impacts on city-region relations. Finally the policy implications and the potential for expanding and planning this network in order to contribute and promote sustainable development of coastal cities will be explored.
Keywords: 330